Experimental colitis does not increase the prevalence of ANKENT, a spontaneous joint disease in mice - Capková, J; Stepánková, R; Hudcovic, T; Sinkora, J; Reháková, Z (Folia microbiologica, 2004)
A possible relationship between intestinal inflammation and joint disease development was investigated. Clinical symptoms of colitis--diarrhea and rectal bleeding--were confirmed by findings of inflammatory processes in the colon in dextran sodium sulfate-treated mice and joint ankylosing enthesopathy (ANKENT) developed in 12.8 % mice with chronic colitis and 13.6 % mice in the control group. Consequently no significant difference in ANKENT frequency was found between mice with and without chronic colitis and the occurrence of ANKENT in both groups was typical for conventional conditions. ANKENT cannot be triggered solely a generalized inflammatory process in the gut.
Keywords: ulcerózní kolitida; klouby nohy (od hlezna dolů); Ankylosis; Prevalence; Disease Models, Animal; myši inbrední C57BL; mužské pohlaví; prevalence; Mice; ankylóza; Colon; modely nemocí na zvířatech; zvířata; Humans; kolon; síran dextranu; myši; Foot Joints; Colitis, Ulcerative; Mice, Inbred C57BL; lidé; Male; Dextran Sulfate; Animals